Innovative Positioning as a Marketing Tool of Retailers on the Food Market - Graażyna Śmigielska; Magdalena Stefańska (Entrepreneurial Business and Economics Review)
Objective: The aim of the paper is to develop the theory of retail business positioning as a part of marketing innovation-based strategy. It is proposed that innovative retail formats and business models should be included in it.